The chosen. Season three [videorecording (DVD)] - Jenkins, Dallas; Swanson, Ryan (Screenwriter); Thompson, Tyler (Screenwriter); Isaac, Shahar; Tabish, Liz, 1986-; Patel, Paras; James, Noah; Xanthis, George Harrison; Roumie, Jonathan, 1974- (Chosen (Television program), 2023)
""Come to me ... I will give you rest." (Matthew 28:11) Jesus promises rest to His followers - but that doesn't mean there won't be trouble along the way. In Season 3 of The Chosen, Jesus sends all 12 disciples on their first mission and they face new fears as well as entrenched, old ways. And each one faces his own unique burden, too: Matthew's estrangement from family, Little James' unhealed disability, Simon Z's unresolved past, and Simon and Eden's marriage crisis- just to name a few. Meanwhile, scores of newcomers like Veronica and Jairus desperately seek Jesus for relief from crushing crises and heavy-handed authorities, religious and Roman. Thousands ultimately converge on Jesus, first to argue then to listen. But as His preaching extends to the next day, they find themselves in a new predicament-far from home, famished, and without any food to eat. Until a little boy with five loaves and two fishes shows up..." -- provided by distributor.